Criminal Liability of Holding Company in Environmental Crime in Indonesia - ALSA, Abdul Aziz; SAMEKTO, F.X. Adji; PUJIYONO, Pujiyono (Journal of Environmental Management and Tourism, 2021)
This study seeks to analyze the form of law enforcement in Indonesia against environmental crimes committed by the parent company, and the criminal liability of the parent company in the event of an environmental crime within the parent company. This research uses library research method and post-positivism paradigm. by collecting data in the form of sources of legal material in the form of legislation, literature, and writings related to this research, processed and analyzed qualitatively. Empirical data was obtained to strengthen the findings. The results showed that there has not been a single law enforcement against holding companies in environmental crimes in Indonesia. The criminal responsibility of an environmental crime within the scope of the holding company is directed to the holding company as the leader and/or the giver of orders; subsidiary as actor; and/or both together.